Foliar application of plant growth regulators on growth, yield and economics of linseed (Linum usitatissimum L.): APPLICATION OF PLANT GROWTH REGULATORS ON GROWTH, YIELD AND ECONOMICS OF LINSEED - S K DWIVEDI; R K SATYARAJ GURU; S PANDA (Journal of Oilseeds Research, 2021)
Growth regulators are widely used in various crops to boost the growth and yield attributing characters and ultimately the yield. The present experiment was carried out during rabi season of 2018-2019 and 2019-2020 at IGKV, Raipur, Chhattisgarh in randomized block design with eight treatments and three replications with an objective of finding out the effect of plant growth regulators on growth, yield attributes and yield of linseed variety RLC-92. The treatments consisted of four plant growth regulators (PGRs) with varied concentrations. Results revealed that the application of plant growth regulators significantly improved the growth, yield attributes and yield of linseed as compared to spray with water. Among the eight treatments, application of auxin @ 1 ppm + GA3 @ 200 ppm (T7) recorded highest growth and yield attributes and seed yield of linseed. The auxin @ 1 ppm + GA3 @ 200 ppm (T7) recorded 26.9% higher seed yield than control (T8) and 15.5 and 11.4% higher seed yield than sole application of auxin @ 1.0 ppm (T1) and GA3 @ 200 ppm (T3) treatments, respectively. However, application of auxin @ 1 ppm + GA3 @ 200 ppm (T7) and GA3 @ 400 ppm (T4) recorded the highest oil content during 2018-19 and 2019-2020, respectively. The maximum oil yield was recorded under the application of GA3 @ 400 ppm (T4) treatment. The application of auxin @ 2.0 ppm (T2) resulted in the highest B:C ratio and was found to be most remunerative for getting good returns.